An online real-time path compensation system for industrial robots based on laser tracker. (30th August 2016) - Shi, Xiaojia; Zhang, Fumin; Qu, Xinghua; Liu, Bailing
Industrial robots have been widely used in many areas for the properties such as low cost, high flexibility and relatively large working space. The low absolute accuracy and low stiffness, however, limit the application in high precision areas. This article presents an approach for industrial robots that overcomes the inaccuracy of robotic path in offline programming. Robot Sensor Interface of KUKA robot controller makes the error compensation available. First, the compensation performance of the KUKA KR5 arc robot is investigated and the straight-line and circular arc path compensation strategies are proposed. Besides, an error compensation algorithm is proposed to generate the compensation values as well as to deal with the oscillation of real-time compensation. Finally, experimental results using a KUKA KR5 arc robot verify the correctness and accuracy of the approach.